Early contractor involvement : improving the management of contract risk - Smith, Michael; Finn, Matthew; Broome, Jon; Maddox, Catherine (Emerald Publishing Limited, 2025)
Early Contractor Involvement: Improving the management of contract risk explains how to structure and administer a process of early contractor involvement within a two-stage tender process. It provides clear practical guidance on the range of factors that need to be considered to achieve the benefits of early contractor involvement (ECI) which includes improved design, pricing and risk management. Drawing on a range of case studies and the authors' first-hand experience, the book gives much-needed practical insight into the optimal use of ECI as a procurement approach. Coverage in the book includes benefits of the ECI process and key steps to ensure the benefits are realised how to administer ECI under an NEC contract and comparison with other contract forms, including JCT targeted advice for the Client, Contractor and Project Manager discussion of commercial considerations, risk allocation and incentives required to deliver the benefits of ECI insights from real-world case studies. Early Contractor Involvement offers practical guidance on a procurement approach that is becoming increasingly popular and will promote best practice within the construction industry. It will be of interest to a range of professionals working in construction procurement, including clients, contractors and project managers, as well as lawyers and professional consultants.